Development and implementation of a centralized surveillance infection prevention program in a multi-facility health system: A quality improvement project. Issue 1 (22nd March 2023) - Snyder, Graham M.; Wagester, Suzanne; Harris, Patricia L.; Valek, Abby L.; Hodges, Jacob C.; Bilderback, Andrew L.; Kader, Fazrina; Tanner, Colleen A.; Metzger, Amy P.; DiNucci, Susan E.; Colaianne, Bonnie V.; Chung, Ashley; et al.
Abstract: Objective: To develop, implement, and evaluate the effectiveness of a unique centralized surveillance infection prevention (CSIP) program. Design: Observational quality improvement project. Setting: An integrated academic healthcare system. Intervention: The CSIP program comprises senior infection preventionists who are responsible for healthcare-associated infection (HAI) surveillance and reporting, allowing local infection preventionists (LIPs) a greater portion of their time to non-surveillance patient safety activities. Four CSIP team members accrued HAI responsibilities at 8 facilities. Methods: We evaluated the effectiveness of the CSIP program using 4 measures: recovery of LIP time, efficiency of surveillance activities by LIPs and CSIP staff, surveys characterizing LIP perception of their effectiveness in HAI reduction, and nursing leaders' perception of LIP effectiveness. Results: The amount of time spent by LIP teams on HAI surveillance was highly variable, while CSIP time commitment and efficiency was steady. Post-CSIP implementation, 76.9% of LIPs agreed that they spend adequate time on inpatient units, compared to 15.4% pre-CSIP; LIPs also reported more time to allot to non-surveillance activities. Nursing leaders reported greater satisfaction with LIP involvement with HAI reduction practices. Conclusion: CSIP programs are a little-reported strategy to ease burden on LIPs with reallocation of HAI surveillance. The analyses presented here will aid health systems in anticipating the benefit of CSIP programs.